Descriptive or critical sociology. The choice is yours - McConville, Mike (The British journal of criminology, 1997)
Discusses a critique of the book `The Case for the Prosecution,' by author David Smith. Basis of his criticism; Use of `simple Marxist argument'; Examination of how Smith misrepresented the book's arguments and perspectives